Multiwavelength brillouin fiber lasers / Mohammadreza Rezazadeh Shirazi - Shirazi, Mohammadreza Rezazadeh (2009)

(untitled)
This thesis describes to solve the problem of higher power generation of Brillouin fiber lasers (BFLs), to measure their linewidth as a challenging issue and to generate multiwavelength Brillouin fiber laser (MBFL) sources as an application of BFL generation in the both linear and ring cavities. By using the proposed ring cavity with the same components used in the conventional ring cavities, a new Brillouin fiber ring laser (BFRL) with higher output power has been generated. The proposed BFRL configuration shows an output peak power of -0.5 dBm, which is 5.7 dB higher compared to the conventional configuration. In the proposed linear cavity, BFL configuration has been demonstrated by incorporating a 3-dB coupler, a 95/5 coupler, two optical circulators, and a 25 km SMF that allows very high conversation efficiency from the Brillouin pump (BP) to the BFL compared with the conventional linear cavity BFL. Stable BFL operation was obtained at an up-shifted wavelength of 0.086 nm from the pump wavelength with the BFL peak power at -1 dBm, which is 12.3 dB higher than the conventional BFL with the same BP power 13 dBm, due to the reduced cavity loss in the proposed configuration. In the MBFL generation, more than 14 and 9 BFL lines are demonstrated in the ring and linear cavities, respectively. In the ring cavity, the both wavelength spacing 0.08 nm (~10 GHz) and 0.16 nm (~20 GHz) are obtained with the bi - directional multi-wavelength generation whereas in the linear cavity only the wavelength spacing 0.08 nm (~10 GHz) is obtained. The used BP powers are about 14 dBm and 11.7 dBm in respectively the ring and linear MBFL generation. By using a Bismuth Erbium doped fiber amplifier (Bi-EDFA) in the linear BFL cavity, multiwavelength Brillouin Erbium fiber laser (MBEFL) has been ii demonstrated in the L band wavelength region (1565-1625 nm). The generated MBEFL has more number of lines (~50 lines) in comparision with the MBFL by using the Bi-EDFA pumped bidirectionaly with two EDFA pump power 125 mW and Brillouin pump power 5 dBm. The MBEFL generation is limited to the Bi- EDFA operational wavelength region (1525-1625 nm) although it is extended to L band region by using Bi-EDFA in comparison with the traditional MBEFL which can be generated only in the C band wavelength region (1525-1565 nm). In addition, multiwavelength Brillouin Raman fiber laser (MBRFL) is also generated by using a Raman amplifier in a BFL cavity with a 25 km single-mode fiber as the nonlinear gain medium. The second and the third Brillouin stoke waves are obtained by using the Raman pump power 150 mW and Brillouin pump 5.5 dBm at the BP wavelength 1568 nm. The anti-Stokes line is also produced due to fourwave mixing phenomenon. The number of MBRFL lines can be increased by using higher Raman pump power in addition to an optical fiber with the higher Raman gain such as dispersion compensating fiber (DCF). As a high coherent light source with ultranarrow linewidth, Brillouin fiber lasers have been used in many applications especially in microwave generation, gyroscopes. BFL linewidth measurement has also been a challenging research due to the ultranarrow BFL linewidth. In this work, the BFL linewidth has been measured 8 Hz and 24 Hz by using BP linewidth 15 MHz and 124 MHz, respectively. This measurement has been done by the heterodyne method between two independent BFLs. The measured BFL linewidth values are in the range a few hertz as expected from the most of the last reports.